INVESTIGATIONS OF APARTMENT HOUSE CELLAR MICROCLIMATE AND IT’S IMPROVEMENT POSSIBILITIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Apartment houses made in the last century in Latvia have rather big heat transfer factor and not good ventilation, especially in cellar. That leads to formation of condensate on building constructions. During cold weather in winter time, this condensate formats ice layer that damages building constructions ant also lead to inconvenience for inhabitants, for example, disturbs opening of cellar door. During investigations the cellar microclimate parameters, such as temperature, humidity and dew point, were measured and different ways to improve them and as result preventing of condensate formation were worked out. The measurements shows that sometimes the air temperature and the temperature on surfaces reaches dew point and therefore the condensate starts to format. The possibilities to eliminate humidity and to increase dew point are worked out during investigations.